Life cycle assessment of greenhouse gases emission from nitrogen fertilizer application in palm oil industry / Norliyana Zin Zawawi - Norliyana, Zin Zawawi (2012)
With the high current demand for palm oil, the production of this fast-growing industry should have minimal impact on the environment. For the purpose of planning and implementing mitigation, detailed information and data on the production processes are required. Thus, a study was conducted to collate data and information on the inputs used throughout the production processes where the scope of study has been confined to oil palm plantation and the utilization of nitrogen fertilizer. Data was collected and calculated using Life Cycle Assessment (LCA) procedures, where environmental impacts and hotspots were identified and greenhouse gases emission from plantation was estimated based on Intergovernmental Panel on Climate Change (IPCC) methodology. The results showed that the production and application of fertilizer was identified as a potential contributor to the environmental impacts. A case study was conducted at the MPOB’s oil palm research station located at Keratong, Pahang to measure nitrous oxide emission from the fields. Fluxes were collected from the oil palm tree which were planted on a mineral soil and fertilized with nitrogen fertilizers namely, ammonium sulphate and urea using closed chamber method. From this study, among the significant environmental impacts for the production of one tonne FFB that could result from the production and application of fertilizers are the depletion in fossil fuels (1.79 Pt), respiratory inorganics (1.26 Pt), climate change (0.45 Pt) and acidification/eutrophication (0.33 Pt) (weighted values, 1 Pt equivalents to the impacts from one-thousandth person per year). From the field measurements, it was found that there was no significant differences in the nitrous oxide fluxes (0.978, p>0.05) emitted from ammonium sulphate (3.61 x 10-3 μg m-2 hr-1) and urea application (3.28 x 10-3 μg m-2 hr-1). The environmental parameters that are highly correlated with nitrous oxide emission are the amount of rainfall (r2=0.756), total N in soil (r2=0.532), soil moisture (r2= 0.527), and percentage of water-filled pore space (%WFPS) (r2= 0.527). From the results of this study it can be concluded that nitrogen fertilizer is a major contributor to environmental impacts and nitrous oxide emission in an oil palm plantation.